2023
DOI: 10.3390/pharmaceutics15010168
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Functionalized Protein Nanocarriers for Cancer Therapy: Recent Developments and Prospects

Abstract: Recently, the potential use of nanoparticles for the targeted delivery of therapeutic and diagnostic agents has garnered increased interest. Several nanoparticle drug delivery systems have been developed for cancer treatment. Typically, protein-based nanocarriers offer several advantages, including biodegradability and biocompatibility. Using genetic engineering or chemical conjugation approaches, well-known naturally occurring protein nanoparticles can be further prepared, engineered, and functionalized in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…Peptides with a positive hydrophobicity scale tend to aggregate in an aqueous solution, and so does the P4 peptide [13,58]. Silica nanoparticles, which are biocompatible and hydrophilic, have been shown to be a promising drug delivery system due to their ability to penetrate tissue systems, facilitate drug uptake by cells and ensure efficient drug delivery to the target site [31][32][33]35,59,60]. Because of their hydrophilic properties, silica nanoparticles can block opsonization and easily move through the blood system [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides with a positive hydrophobicity scale tend to aggregate in an aqueous solution, and so does the P4 peptide [13,58]. Silica nanoparticles, which are biocompatible and hydrophilic, have been shown to be a promising drug delivery system due to their ability to penetrate tissue systems, facilitate drug uptake by cells and ensure efficient drug delivery to the target site [31][32][33]35,59,60]. Because of their hydrophilic properties, silica nanoparticles can block opsonization and easily move through the blood system [61].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, biomimetic silica condensation, wherein peptides or proteins capable of silica deposition produce silica nanoparticles from silicic acid under ambient conditions, has received significant attention as a system that could efficiently load and deliver payloads insitu. [30][31][32][33][34][35]. Previously, we demonstrated that BMP2 could deposit biomimetic silica [36].…”
Section: Introductionmentioning
confidence: 98%
“…Nanoparticles fabricated from proteins such as albumin have good biocompatibility and biodegradability. 39 As natural materials, they are generally nontoxic and do not elicit unwanted immunological responses. 40 Albumin is particularly attractive due to the presence of numerous functional groups, which enable modifications as well as high thermal and aqueous solution stability.…”
Section: Protein Nanoparticlesmentioning
confidence: 99%
“…The contact angle of the mimicked surface was 40.1 • greater than that of the pure surface, confirming its excellent hydrophobic properties (Figure 8c). Nanomaterials and substances have been applied in biomimetics due to their similar structures and sizes to molecules, providing various approaches to cell or tissue compartments [117,118]. To utilize this opportunity, numerous studies are conducting nano biomimetic research inspired by the properties, structures, and applications of nanomaterials.…”
Section: Wound Care Techniques Inspired By Plantsmentioning
confidence: 99%